2019
DOI: 10.1186/s40623-019-1094-7
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of polar cap patches with a low-cost airglow camera: pilot observations in Svalbard, Norway

Abstract: We evaluate the capability of a low-cost all-sky imager (ASI), which has been operative in Longyearbyen (78.1° N, 15.5° E), Norway, to detect 630.0 nm airglow signatures of polar cap patches. The ASI is composed of a small camera, with a charge-coupled device (CCD), manufactured by Watec Co. Ltd., a fish-eye lens, and an optical filter whose central wavelength is 632.0 nm and full-width half maximum (FWHM) is 10 nm. In Longyearbyen, another ASI equipped with a cooled electron-multiplying charge-coupled device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 1984 ; Hosokawa et al. 2014 , 2016 , 2019 ). On the nightside the airglow patches leave the polar cap and enter the nightside auroral oval (Lorentzen et al.…”
Section: Geoeffects Of Dayside Transientsmentioning
confidence: 99%
See 1 more Smart Citation
“… 1984 ; Hosokawa et al. 2014 , 2016 , 2019 ). On the nightside the airglow patches leave the polar cap and enter the nightside auroral oval (Lorentzen et al.…”
Section: Geoeffects Of Dayside Transientsmentioning
confidence: 99%
“…Intense PMAF activity can also cause significant phase scintillation and loss of signal lock for satellite navigation signals . Recombination of the high-density plasma leads to weak 630.0 nm emissions that can be observed as airglow patches (Weber et al 1984;Hosokawa et al 2014Hosokawa et al , 2016Hosokawa et al , 2019. On the nightside the airglow patches leave the polar cap and enter the nightside auroral oval (Lorentzen et al 2004;Van Der Meeren et al 2015).…”
Section: Ionospheric Flow Response To Ftesmentioning
confidence: 99%
“…Similar small and low-cost ASIs have been deployed and installed into several places in the polar region in both hemispheres (Ogawa et al 2020). Hosokawa et al (2019) used one of the ASIs at Longyearbyen in Svalbard, Norway and confirmed its capability of detecting faint airglow signatures of polar cap patches whose airglow intensity is a few hundreds of Rayleigh. As a next step, we carried out a pilot observation at low latitudes to evaluate the feasibility of utilizing the ASIs for monitoring EPBs.…”
Section: Introductionmentioning
confidence: 93%
“…Hence, the derived absolute optical intensity in Rayleigh includes a certain contribution of background continuum emission. However, Hosokawa et al (2019) pointed out that the offset is ~ 20 R for the cases of airglow observations in the polar cap region.…”
Section: Experimental Arrangement Of the Pilot Observationsmentioning
confidence: 99%
See 1 more Smart Citation